Peningkatan Usaha Masyarakat Kalibaru Melalui Pengolahan Limbah Cangkang Kerang Hijau menjadi Paving Block - Ria Kusumaningrum; Rully Trihantana; Tubagus Rifky Thantawi (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
Kalibaru, Cilincing subdistrict is located on the sea coast of Jakarta and the livelihoods of its residents are mostly fishermen. This Kalibaru village produces shells that are quite large, so they create a lot of shellfish waste as a by-product. In tackling this waste by making it one of the basic ingredients for making paving blocks, considering that shells have CaO lime compounds, the percentage of which is 66.70% for cement manufacturing raw materials. This activity aims to empower residents through the establishment of a shellfish waste processing business into paving blocks. The method used in this activity is a participatory approach for adults through lectures, training and assistance in its establishment and management, and invites participants to be more creative and innovative in producing products. The result of this activity is that the community develops a business of processing shellfish waste into paving blocks to support the management of shellfish waste and increase community income. But overall this activity must be continued again to achieve its original goal.